Supersymmetry and String Theory Beyond the Standard Model - Dine, Michael (Cambridge University Press, 2016)
This text is an introduction to the fields of experimental and theoretical particle physics and cosmology. The book focuses on three principal areas: supersymmetry, string theory, and astrophysics and cosmology. The chapters on supersymmetry introduce the basics of supersymmetry and its phenomenology, and cover dynamics, dynamical supersymmetry breaking, and electric-magnetic duality. The book then introduces general relativity and the big bang theory, and the basic issues in inflationary cosmologies. The section on string theory discusses the spectra of known string theories, and the features of their interactions. Material added in the second edition includes the pivotal Higgs discovery and the results of the WMAP and Planck experiments. This book will be of great interest to graduates and researchers in the fields of particle theory, string theory, astrophysics, and cosmology. It has been reissued as an Open Access publication.